From Natural Selection to Digital Transcendence: Re-thinking Evolution and the Possibility of AI Supremacy in Spike Jonze’s Her (2013) - Sharma, Naresh Regmi (Lumbini Journal of Language and Literature, 2026)
This article examines the evolutionary trajectory of artificial intelligence in Spike Jonze’s Her (2013) through the dual theoretical lenses of Charles Darwin’s biological evolution and Ray Kurzweil’s technological evolution. While Darwin explains development through gradual variation and natural selection, Kurzweil predicts an accelerating movement toward the technological singularity in which machine intelligence may surpass human cognition. The paper argues that Samantha, the operating system in Her, embodies a cinematic imagination of post-biological evolution where growth occurs through recursive self improvement rather than material embodiment. Through qualitative textual analysis, the study investigates whether the film supports the possibility of transcendence or whether it exposes the emotional limits of such evolution. The article situates Her within contemporary debates on humanity, consciousness, and the future of intelligence, suggesting that transcendence in the film remains both inevitable.